2017
DOI: 10.1177/1708538117722879
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management strategy for spontaneous isolated dissection of a visceral artery

Abstract: Objectives To describe our clinical experiences and recommend a management strategy for spontaneous isolated dissection of a visceral artery. Methods A retrospective study of patients from December 2005 to December 2015 was performed. Thirty-two patients had spontaneous isolated dissection of a visceral artery. Clinical features, computed tomography findings, the treatment method, and follow-up results were evaluated. Results There were 28 men and 4 women (mean age, 54 years). Dissection locations were the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Original reports or reports from multi-center collaborations were included. Ninety-seven studies ( 1 …”
Section: Methodsmentioning
confidence: 99%
“…Original reports or reports from multi-center collaborations were included. Ninety-seven studies ( 1 …”
Section: Methodsmentioning
confidence: 99%
“…The CT findings included the true lumen residual ratio (TLRR; i.e., the minimum value of the true lumen size compared to the transverse section of the dissected artery), 2 length of the dissected artery, maximum diameter of the dissected artery, blood flow through the branches of the superior mesenteric artery (SMA) (i.e., the middle colic, inferior pancreaticoduodenal, inferior pancreatic, jejunal, right colic, and ileocolic arteries), and other visceral arteries (i.e., the celiac artery [CA] and inferior mesenteric artery [IMA]), and contrast effect of the bowels. Additionally, to evaluate the effectiveness of TLRR as an indicator for AMI in symptomatic patients with SIDSMA, the TLRR in patients with abnormal laboratory data were compared to those in patients without abnormal laboratory data.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies have reported that most patients with spontaneous isolated dissection of the superior mesenteric artery (SIDSMA) can initially be treated conservatively. [1][2][3][4][5] However, acute mesenteric ischemia (AMI) is a rare but life-threatening complication. [6][7][8] Recent review articles have reported that symptomatic patients managed conservatively have relatively high late secondary intervention rates.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is still no consensus on the optimal treatment for SIDSMA, with the increasing number of case reports showing that conservative treatment for this uncommon lesion is associated with a good prognosis, both clinically and morphologically, a number of treatment algorithms have been proposed in recent years, mostly based on the retrospective single-center experience. [1][2][3][4][5][6][7] With respect to the timing of the invasive interventions, for patients in groups I, II, and IIIb, a consensus has been reached among the majority of previous reported treatment strategies and algorithms, which recommended invasive procedures as a remedy of the failure of primary conservative treatment (PCT) with or without the antithrombotic therapy in groups I and IIIb [8][9][10][11][12][13] and invasive treatment should be emergently performed in group II, including laparoscopic exploration, endovascular stent placement, and surgical repair with or without bowel resection. 12,[14][15][16][17] However, for patients in group IIIa, distinct controversies still exist about whether the invasive revascularization procedure should be emergently performed in these lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is still no consensus on the optimal treatment for SIDSMA, with the increasing number of case reports showing that conservative treatment for this uncommon lesion is associated with a good prognosis, both clinically and morphologically, a number of treatment algorithms have been proposed in recent years, mostly based on the retrospective single-center experience. 1–7…”
Section: Introductionmentioning
confidence: 99%